2003
DOI: 10.1007/978-3-540-40968-7_4
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics without Time for Quantum Gravity: Covariant Hamiltonian Formalism and Hamilton-Jacobi Equation on the Space G

Abstract: Hamiltonian mechanics of field theory can be formulated in a generally covariant and background independent manner over a finite dimensional extended configuration space. The physical symplectic structure of the theory can then be defined over a space G of three-dimensional surfaces without boundary, in the extended configuration space. These surfaces provide a preferred over-coordinatization of phase space. I consider the covariant form of the Hamilton-Jacobi equation on G, and a canonical function S on G whi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…(A7) 23 One may show this using the formula for acceleration (3.17) and the requirement that n µ have unit norm.…”
Section: Some Preliminary Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(A7) 23 One may show this using the formula for acceleration (3.17) and the requirement that n µ have unit norm.…”
Section: Some Preliminary Resultsmentioning
confidence: 99%
“…where we have made a substitution in (4.56) using (4.55). It is common to identify (4.56) as the Hamilton-Jacobi equation for (vacuum) GR, as is often done in the literature [21,23,29], and it may be shown that (4.56) define the dynamics for (vacuum) GR [22]. We note that equations (4.56) do not form the Hamilton-Jacobi equation for GR in the same sense as the Hamilton-Jacobi equation in mechanics; H gf is a Hamiltonian density, not a Hamiltonian, so (4.56) should be viewed as a set of local constraints.…”
Section: The Weiss Variationmentioning
confidence: 99%
“…In particular, there is a Hamiltonian system on boundary data (see [32]). Rovelli [38] showed that this considerations can be generalized (in a covariant way) to any classical field theory. In particular he was able to write down a Hamilton-Jacobi equation on the space of boundary data of the field equations and show that the action functional provide a canonical solution.…”
Section: 34mentioning
confidence: 94%
“…Unfortunately, there is no consensus on a covariant Hamiltonian framework for field theories and different approaches often differ on details; see [2], [3], [4], [5], [6], [7], [8], [9].…”
Section: Introductionmentioning
confidence: 99%